Anhedonic Type Behavior and Anxiety Profile of Wistar-UIS Rats Subjected to Chronic Social Isolation - Acero-Castillo, María Camila; Ardila-Figueroa, María Camila; Botelho de Oliveira, Silvia (Frontiers in Behavioral Neuroscience, 2021)
Chronic Social Isolation (CSI) is a model of prolonged stress employed in a variety of studies to induce depression and anxious behaviour in rats. The present study aims to evaluate the effect of CSI on male Wistar rats in terms of “anhedonic-type” behaviour in the Sucrose Preference Test (SPT) and anxiogenic profile in the elevated-plus-maze (EPM) test, as well as evaluating the effect of resocialization upon sucrose consumption. A total of 24 adolescent male Wistar rats were evaluated. The animals were housed either together (communally) or socially isolated for 21 days, and then exposed for 4 consecutive days to the SPT test (water vs. a 32% sucrose solution [SS]). Four days later, they were again subjected to the SPT test (32% vs. 0.7% SS), and then tested on the EPM apparatus 3 days later. Following the completion of the anxiogenic profile of the model, the animals were resocialized for 72 hours and then re-tested once again using the SPT (32% vs. 0.7% SS). Twenty-four hours after this final consumption, the animals were euthanized to record the weight of their adrenal glands (AG). It was found that exposure to CSI produces anhedonic-type behaviour and an anxiogenic profile in adolescent male rats, as evidenced in both the SPT and EPM tests, as well as in the animals’ physiological stress response. It was also demonstrated that resocialization does not reverse the anhedonic-type behaviour, nor the physiological response to stress.